Preparation and validation of the content of an instrument to assess the quality of services of reception with risk classification in obstetrics. - Dannielly Azevedo de Oliveira; Douglissandra de Morais Ferreira; Lilian Lira Lisboa; Thaiza Teixeira Xavier Nobre (PLoS ONE)
Introduction The expectations and needs of users and those assisting determine the quality of services. It becomes a priority to understand how all elements involved in the care process perceive the quality of the services offered, aiming to intervene promptly and organize them to satisfy the needs of both and improve the assistance provided. Objective To develop and carry out content validation of an instrument for evaluating the quality of the Reception service with Risk Classification in obstetrics with evaluation dimensions for users, health professionals, and managers. Methodology This is a methodological study for constructing and validating content. Consider the Pasquali Model, following the theoretical pole's component steps and the empirical's beginning. An instrument was created and divided into 3 modules: with a dimension for the user (module 1), health workers (module 2), and manager (module 3), created based on the theoretical framework according to Donabedian and the objectives proposed by the World Health Organization and Brazilian Ministry of Health. Validated for content by a committee of judges (experts) specializing in the area of the instrument. The analysis was carried out based on the committee's agreement rate, Content Validity Index (CVI), and Kappa index for the evaluation and achievement of the ideal parameters of agreement and content validity of the tool among the judges. Results The results suggest that the tool has good content validity. CVI, Kappa, and CI were evaluated above 0.8. Item values considered lower than 0.8 were excluded. Conclusion The results suggest that the tool has good content validity, and the pilot test stage can be continued to complete the validation process.